Unifying CSR and Responsibility Accounting: Towards an Integrated Accountability Framework - Špogienė, Gintarė; Holovash, Bohdan; Holovash, Liliia (Buhalterinės apskaitos teorija ir praktika, 2025)
Traditional responsibility accounting and accountability frameworks often lack integration of corporate social responsibility, despite corporate social responsibility being considered a paramount of modern business practice. Business managers increasingly face challenges when balancing various often competing stakeholder interests in complex and dynamic environments, which complicates high-quality decision-making. This study reviews and synthesizes academic literature on responsibility accounting and CSR to identify the strengths and limitations of conventional accountability systems and to explore the underlying motivations behind socially responsible management. The aim of this study is to propose an integrated accountability framework which includes not only financial goal setting and tracking, but also socially responsible management evaluation and decisions. Societal expectations from businesses have significantly increased, but corporate social responsibility is often perceived as a company’s promotional asset or image-enhancement strategy aimed at boosting profitability, which fundamentally contradicts the principles of socially responsible business. Corporate social responsibility should not be evaluated in isolation from overall business performance. To ensure that CSR serves as a genuine driver of sustainable economic development rather than a symbolic gesture, it must be embedded within the broader performance management system. The proposed framework emphasizes the need to integrate CSR throughout all key management processes, including organizational structure analysis, responsibility center goal-setting, performance evaluation, and accountability control.